Challenges of Quality Assesment System (QLASSIC) in Malaysia's construction industry - Azmi, Nurul Aidah (2022)
Quality is an essential aspect of the construction industry, especially in Malaysia. To quantify and assess quality in construction, Construction Industry Development Board (CIDB) has introduced the Quality Assessment System in Construction (QLASSIC) as a standard quality measure of in the Malaysian construction industry. This research mainly aims to assess the challenges of QLASSIC and its implementation by contractors registered under CIDB Malaysia for construction projects to achieve the standard of quality in construction and avoid building failure. The first specific objective of this research study is to identify the advantages of the implementation of the QLASSIC system. Secondly, to determine the challenges in the implementation of QLASSIC by the contractors in the construction industry and the last objective is to suggest strategies to overcome the challenges in QLASSIC implementation for the contractors. A quantitative method was used to achieve the research objectives where data collections from 59 out of 122 respondents in contractors' firms were gathered through a questionnaire. Then, the raw data was analyzed by using the Statistical Package for Social Science (SPSS). From the findings, QLASSIC could successfully reduce the number of major defects and building failure issues as the advantages of the implementation of the QLASSIC system.